(3SjchdhLjG GdEOGQI GdYGeI (B/s - (3aGjR, YHO Gddg MSjfs ((3YeGf (B:s (3OGQ CSGeI ddfTQ hGdJhRjY ,s, 2007)
(3YQVJ GdEOGQI GdYGeI Edi JZjQGJ cKjQI cGfJ LOdkG Hjf GdQaV hGdbHhd, EdG Cf XgQJ Chd EOGQI YGeI HTcd eSJbd HYO GdMQH GdYGdejI GdKGfjI hjYJHQ eSGgeI GdcJGH GdKdGKI (B((3gjQHQJ SGjehf (B- (3hGdOh (B- (3Hh CHd HGj(B) (3cHjQI aj NOeI GdYed ceGOI aGYdI dEYGOI gjcdI GdEOGQI GdYGeI(B. (3hGSJeQJ GdEOGQI GdYGeI HGdJWhQ hGdJbOe Edi GdBf hCUHM GdJQcjR GdhMjO dgG gh EjLGO WQjbI ddJhGab hGdJhGRf Hjf GdJCKjQGJ GdSjGSjI hGdEOGQjI hGdbGfhfjI hGdELJeGYjI hGdeGdjI hGdSdhcjI hGdJcfhdhLjGhgPG eG HMKg GdeDda aj gPG GdcJGH(B. (3MjK bSe GdcJGH Edi KdGKI YTQ aUdkG Ydi GdfMh GdJGdj(B: (3GdaUd GdChd(B: (3hjJMOK Yf eONd GdEOGQI GdYGeI, GdaUd GdKGfj(B: (3hjJMOK Yf Gdgjcd GdJfXjej ddEOGQI GdYGeI, GdaUd GdKGdK(B: (3hjJMOK Yf fXQjI GdEOGQI GdYGeI hGdaUd Hjf GdSdWGJ, GdaUd GdQGHY(B: (3hjJMOK Yf GdJOQjH aj GdEOGQI GdYGeI, GdaUd GdNGeS(B: (3hjJMOK Yf TDhf GdehXajf aj GdbWGY GdYGe, GdaUd GdSGOS(B: (3hjJMOK Yf GdEOGQI GdESJQGJjLjI aj GdbWGY GdYGe, GdaUd GdSGHY(B: (3hjJMOK Yf GdehGRfI GdYGeI aj GdeGdjI GdYGeI, GdaUd GdKGef(B: (3hjJMOK Yf GdSjGSI hGdEOGQI, GdaUd GdJGSY(B: (3jJMOK Yf fXQjI GdJZjQ GdeNWW dg hJWHjbg, GdaUd GdYGTQ(B: (3hjJMOK Yf UfY GdbQGQ (B((3OQGSI aj SjchdhLjG GdEOGQI(B)(3, GdaUd GdMGOj YTQ(B: (3hjJMOK Yf GdEOQGc hGdYRh aj GdSdhc GdJfXjej, GdaUd GdKGfj YTQ(B: (3hjJMOK Yf GdEJUGd aj GdefXeGJ GdEOGQjI, GdaUd GdKGdK YTQ(B: (3hjJMOK Yf GdEUdGM GdEOGQj aj GdhWf GdYQHj(B.s
(3HHdjhZQGajG (B: (3U(B.251-263s
Keywords: (3SjchdhLjGs